Social business by design transformative social media strategies for the connected company - Hinchcliffe, Dion.; Kim, Peter, 1974-; ebrary, Inc. (San Francisco : Jossey-Bass, 2012)
"How to rethink modern organizations for the social media eraSocial Business by Design begins by exploring how the social, cultural, and technological trends provoked by the social media explosion are transforming the business environment. From this big picture view, the book then steps down to closely analyze the various tools of social media strategy: social media marketing, social product development, crowdsourcing, social customer research management, and more. The author then shows how to choose and implement a social business strategy and reveals the exact playbook to maximize its impact. These strategies are grounded in real-world examples from high-profile organizations such as Accenture, Best Buy, DIA, GEICO, ING, LG, Missile Defense Agency, Gucci, World Bank, and IBM.Social Business by Design draws on the rich unique set of assets of the Dachis Group. With a leading consulting business for numerous senior executive clients in Fortune 500 and Global 2000 companies, Dachis uses its "front row" seat in the industry to complete research work with large enterprises in their industry-leading Social Business Council. The books combines compelling explanation, hard-hitting research, and strategic recommendation, very much in line with the way Dachis practices"--
pt. 1. Adapting organizations to the twenty-first century -- pt. 2. The techniques of social business -- pt. 3. Social business design and strategy.
Includes bibliographical references and index.
Electronic reproduction.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Social media -- Marketing; Strategic planning; Electronic books